Linking nitrogen- and straw-sensitive indicator species and their co-occurrences to priming effect in agricultural soil exposed to long-term nitrogen fertilization. (January 2023) - Chen, Hao; Li, Wenjuan; Zheng, Wanning; Yin, Chang; Fan, Xiaoping; Ye, Mujun; Gao, Zixiang; Wu, Chunyan; Liang, Yongchao
Abstract: The increasing input of nitrogen (N) fertilizers has a considerable impact on agricultural soil carbon (C) cycling due to its influence on soil microbial abundance and assemblages. However, the microbial mechanism underlying the response of straw-induced priming effect to long-term N application remains an open question. Here, using soils with three N fertilization levels (0, 300, and 570 kg N ha −1  y −1 ) from a long-term experimental site, we established a 40-day microcosm experiment to investigate the priming effect of straw addition on SOM mineralization and the associated microbial activity and community composition. We found that long-term N application significantly inhibited soil respiration while increasing straw-induced priming effect. The soil microbial biomass (including bacterial and fungal abundance) decreased with increasing N levels, accompanied by decreased bacterial α -diversity and altered β -diversity. In addition, the N fertilization level significantly influenced bacterial and fungal indicator species that were sensitive to straw addition ( si OTUs) and long-term N fertilization ( ni OTUs), as well as their co-occurrence patterns. In the first three days of straw decomposition, long-term N fertilization decreased the oligotroph-to-copiotroph ratio of bacterial si OTUs. In contrast, long-term N fertilization increased this ratio on days 20 and 40, along with facilitated microbial investment in extracellular enzymes and microbial N demand. This caused a stronger "N mining" process and consequently enhanced the priming effect in soil exposed to long-term N fertilization at the later stage of incubation. Linking indicator species analysis with priming effect, these results advance our understanding of the complex C cycling in agricultural soils undergoing long-term nitrogen management. Highlights: N fertilization increased the relative abundance of specific copiotrophic bacteria. The composition of indicator OTUs was determined by N fertilization level. N fertilization level altered the co-occurrence patterns of indicator OTUs. Response of straw-indicator OTUs to N fertilization echoed the change of priming effect.